2011
DOI: 10.1177/1420326x11411954
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Large-scale Production of Marijuana in Residential Buildings

Abstract: Based on the data from the breadth of Canada (∼4300 km), one-third of Canadian homes have ventilation rates below the recommended standard of 0.3 air changes per hour and are at risk for moisture problems. For the purposes of this investigation, a literature review was performed on the health risks associated with exposure to living and drying marijuana plants and the fungi associated with large numbers of indoor plantings. Analysis was made of the impact on Canadian homes if used to grow marijuana. These are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…and Aspergillus sp., were also identified as the most frequent mold species in illicit indoor cannabis plantations in the USA (7,15) and Canada (5). In Canada, on cannabis flower buds, Aspergillus fumigatus was the most frequently found mold species (5). In their study on 30 indoor cannabis plantations in the USA, Martyny et al (7) further found Cladosporium sp.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…and Aspergillus sp., were also identified as the most frequent mold species in illicit indoor cannabis plantations in the USA (7,15) and Canada (5). In Canada, on cannabis flower buds, Aspergillus fumigatus was the most frequently found mold species (5). In their study on 30 indoor cannabis plantations in the USA, Martyny et al (7) further found Cladosporium sp.…”
Section: Discussionmentioning
confidence: 97%
“…The most frequently found mold species in our study, Penicillium sp. and Aspergillus sp., were also identified as the most frequent mold species in illicit indoor cannabis plantations in the USA (7,15) and Canada (5). In Canada, on cannabis flower buds, Aspergillus fumigatus was the most frequently found mold species (5).…”
Section: Discussionmentioning
confidence: 99%
“…(2,(4)(5)(6)(7)(8) Many law enforcement agencies, especially in Canada, have indicated that specific PPE must be worn to protect responders entering IMGOs. (2,5,12,13) This study was conducted to identify the hazards associated with IMGOs in Colorado and to suggest appropriate PPE for entry by law enforcement officers..…”
Section: Discussionmentioning
confidence: 99%
“…Johnson and Miller (6,8) conclude that increased moisture levels in IMGOs likely cause elevated mold spore levels that could be associated with allergic reactions and allergic bronchopulmonary aspergillosis as well as fungal infections. The Institute of Medicine (IOM) and World Health Organization (WHO) have indicated that the presence of mold in damp indoor environments is associated with upper respiratory symptoms, wheeze, cough, asthma symptoms in sensitized individuals, and hypersensitivity pneumonitis.…”
mentioning
confidence: 97%
See 1 more Smart Citation